“Stable” vs. “silent progressive multiple sclerosis”: a real-world retrospective clinical imaging Brazilian study - FIGUEIRA, Gustavo Medeiros Andrade; SOARES, Paula Vallegas; SILVEIRA, Raquel Custodio da; FIGUEIRA, Fernando Faria Andrade (Arquivos de Neuro-Psiquiatria, 2022)
Background: Clinical and imaging are required to characterize activity and progression in MS. The parameters for activity are well defined but not those for progression. The ideal aim for long-term treatment is that neither clinical nor imaging signs of disease should be present, and also no brain atrophy. Objectives: To conduct a comparative clinical-imaging study focusing on MRI brain volumetry. Methods: 174 consecutive relapsing-remitting MS patients (McDonald 2001) were studied, focusing on activity and progression. Annual clinical evaluations (relapse rate and EDSS) and MRI data, along with the annualized evolution of the corpus callosum index (CCI), were compared. Results: Out of 174 patients, 148 were considered clinically “stable” based on EDSS. However, 33 (22.2%) out of this group showed annualized reductions in CCI of more than 0.5%, which was the cutoff for defining significant brain atrophy. Conclusions: Among apparently “stable” relapsing-remitting MS patients, 1/5 showed significant brain atrophy over a follow-up period of at least 7 years. We consider it reasonable to suggest that MRI volume sequences should be included in follow-up protocols, so as to provide information on the real treatment response status.
Keywords: Multiple Sclerosis; Neuroimaging; Corpus Callosum